Functional gold nanoparticle-based antibacterial agents for nosocomial and antibiotic-resistant bacteria. (October 2016) - Kuo, Yen-Ling; Wang, Sin-Ge; Wu, Ching-Yi; Lee, Kai-Chieh; Jao, Chan-Jung; Chou, Shiu-Huey; Chen, Yu-Chie
Aim: Medical treatments for bacterial-infections have become challenging because of the emergence of antibiotic-resistant bacterial strains. Thus, new therapeutics and antibiotics must be developed.Materials & methods: Arginine and tryptophan can target negatively-charged bacteria and penetrate bacterial cell membrane, respectively. Synthetic-peptides containing arginine, tryptophan and cysteine termini, in other words, (DVFLG)2 REEW4 C and (DVFLG)2 REEW2 C, as starting materials were mixed with aqueous tetrachloroauric acid to generate peptide-immobilized gold nanoparticles (i.e., [DVFLG]2 REEW4 C-AuNPs and [DVFLG]2 REEW2 C-AuNPs) through one-pot reactions.Results & discussion: The peptide immobilized AuNPs exhibit targeting capacity and antibacterial activity. Furthermore, (DVFLG)2 REEW4 C-AuNPs immobilized with a higher number of tryptophan molecules possess more effective antibacterial capacity than (DVFLG)2 REEW2 C-AuNPs. Nevertheless, they are not harmful for animal cells. The feasibility of using the peptide-AuNPs to inhibit the cell growth of bacterium-infected macrophages was demonstrated.Conclusion: These results suggested that the proposed antibacterial AuNPs are effective antibacterial agents for Staphylococci, Enterococci and antibiotic-resistant bacterial strains.